The Effect of Commitment, Work Discipline, and Work Culture on Job Satisfaction of Employees of the Cooperative and Umkm Office of Central Sulawesi Province - Sudirman, Adrian; I Nyoman Swedana; Lahmuddin Hamid (The Journal of Management, Digital Business, and Entrepreneurship, 2023)
This study examines the effect of Commitment, work discipline, and organizational culture on the job satisfaction of Cooperative and UMKM Office employees of Central Sulawesi Province. This research uses a descriptive verification approach with quantitative methods through a questionnaire prepared based on the theoretical indicators of each variable. The study population was all civil servants (PNS), as many as 64 people, and the sample was determined using the Slovin formula with an error rate of 5%, so 39 respondents were obtained. The sampling technique was carried out by simple random sampling to ensure representativeness. The data collected were analyzed using multiple linear regression to determine each independent variable's simultaneous and partial effects on job satisfaction. The results showed that the three independent variables-commitment, work discipline, and organizational culture-had a positive and significant effect on employee job satisfaction, both partially and simultaneously. Employee commitment has the most dominant influence, followed by organizational culture and work discipline. Classical assumption tests, including normality, multicollinearity, heteroscedasticity, and autocorrelation tests, also show that the regression model meets the basic statistical assumptions so that the research results can be interpreted validly. The findings confirm the importance of fostering Commitment and strengthening organizational values to create a healthy, productive, and satisfying work environment.